2014
DOI: 10.1080/13571516.2014.950476
|View full text |Cite
|
Sign up to set email alerts
|

Product Differentiation, the Volume of Trade and Profits under Cournot and Bertrand Duopoly

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
(13 reference statements)
0
5
0
Order By: Relevance
“…In the previous literature (Ashournia et al 2013;Bernhofen 2001;Brander 1981;Brander and Krugman 1983;Chang and Xiao 2015;Clarke and Collie 2003;Collie 1996;Collie and Le 2014;Cordella 1993;Friberg and Ganslandt 2005;Fujiwara 2009; Kawabata and Takarada 2015; Kawabata et al 2010;Kiyotaki and Miyakawa 2013;Krzysztof 2016;Saggi 2006;Yamamoto 2014;Yang and Kyung 2014), it can be observed that when exploring the effect of trade liberalization on welfare, there is a gap for the case of Bertrand competition under asymmetric country. There could be very few studies that follow these conditions; however, there is no single study that analyses the effect of trade liberalization on all three countries under Bertrand competition for the asymmetric countries.…”
Section: Two Shortcomings Of Previous Studiesmentioning
confidence: 98%
See 2 more Smart Citations
“…In the previous literature (Ashournia et al 2013;Bernhofen 2001;Brander 1981;Brander and Krugman 1983;Chang and Xiao 2015;Clarke and Collie 2003;Collie 1996;Collie and Le 2014;Cordella 1993;Friberg and Ganslandt 2005;Fujiwara 2009; Kawabata and Takarada 2015; Kawabata et al 2010;Kiyotaki and Miyakawa 2013;Krzysztof 2016;Saggi 2006;Yamamoto 2014;Yang and Kyung 2014), it can be observed that when exploring the effect of trade liberalization on welfare, there is a gap for the case of Bertrand competition under asymmetric country. There could be very few studies that follow these conditions; however, there is no single study that analyses the effect of trade liberalization on all three countries under Bertrand competition for the asymmetric countries.…”
Section: Two Shortcomings Of Previous Studiesmentioning
confidence: 98%
“…While the autarky equilibrium can be adequately competitive. While considering the Bertrand competition most of the studies hold the assumption of symmetric countries size (Ashournia et al 2013;Collie and Le 2014;Kawabata and Takarada 2015;Yang and Kyung 2014) however few of them take the assumption of asymmetric country size. For the case of symmetric country size, Kawabata and Takarada (2015) consider a model of three markets for Bertrand and Cournot competition in differentiated oligopolies and find out the impact of FTAs on the welfare of the countries.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Bernhofen (2001) introduced product differentiation into Cournot and Bertrand oligopoly models of intra-industry trade, focusing on the effects of trade on profits and consumer surplus. The effects of trade costs in related models have also been considered by Anderson, Donsimoni, and Gabszewicz (1989), Brander and Spencer (2015) and Collie and Le (2015). Clarke and Collie (2003), and Gandslandt (2006, 2008) have explored gains from trade under Bertrand competition.…”
Section: Introductionmentioning
confidence: 99%
“…Bernhofen (2001) introduced product differentiation into Cournot and Bertrand oligopoly models of intra-industry trade, focusing on the effects of trade on profits and consumer surplus. The effects of trade costs in related models have also been considered by Anderson, Donsimoni, and Gabszewicz (1989), Brander and Spencer (2015) and Collie and Le (2015). Clarke and Collie (2003), and Gandslandt (2006, 2008) have explored gains from trade under Bertrand competition.…”
Section: Introductionmentioning
confidence: 99%